The Effect of Daniel’s Model for Brain Dominance (Right – Left) On Leaning Handstand in Artistic Gymnastics for second grade college Students - Sahebb, Murtadha; Salih, Ayad (Journal of Physical Education, 2023)
The research aimed at identifying the effect of Dainel’s model for brain dominance (right – left) in handstand skill for second grade college students during artistic gymnastics for men. The researchers used the experimental method on (80) sophomore students from physical education and sport sciences department/ college of Al Israa University for the academic year 2021 - 2022. The subjects were (20) students from section A as an experimental group and (20) students from section B as controlling group so as to identify their brain hemispheres. Each group was subdivided into two groups; left and right hemisphere. The data was collected and treated using SPSS to conclude that Daniel’s model for brain dominance (right - left) have significant effect on developing handstand in men’s artistic gymnastics. Finally they recommended using teaching models for learning handstand and other skills in artistic gymnastics for men.